What Does #Freedom Look Like? Instagram and the Visual Imagination of Values. (27th August 2021) - Trillò, Tommaso; Scharlach, Rebecca; Hallinan, Blake; Kim, Bumsoo; Mizoroki, Saki; Frosh, Paul; Shifman, Limor
Abstract: Instagram is the place for the visualization of everything, from travel and food to abstract concepts such as freedom. Over the past decade, the platform has introduced a bottom-up process where users co-produce image repertoires that shape the boundaries of the imaginable. Drawing on an epistemology of social constructionism, we ask which visual repertoires are associated with value-related terms on Instagram. We studied 20 widely used value hashtags, sampling the top 100 posts for each (N = 2, 000). A combined qualitative–quantitative content analysis revealed that 19 of the 20 hashtags possess distinct visual footprints, typically reflecting an orientation toward the self and an emphasis on consumption. We conclude by discussing three implications of our findings: the role of images in the social construction of the meaning of values, the distinction between internalized and externalized value depictions, and aestheticized consumption as an organizing principle of Instagram's mainstream.